Study on triaxial mechanical behavior and energy evolution of composite rock with coplanar double fractures - Yujie SI; Taoli XIAO; Hao YUAN; Haicheng SHE; Yunfeng ZHAO (Meitan kexue jishu)
In a large number of deep rock mass engineering, there is widespread contact between rocks with different properties, forming typical composite rock masses locally. The fracture configuration properties and confining pressure have a significant impact on the mechanical behavior, energy evolution, and crack propagation law of composite rock. In order to study the effects of fracture configuration properties and confining pressure on the mechanical behavior, energy, and microcrackevolution of composite rock, based on indoor uniaxial and triaxial compression tests, a triaxial compression particle model of composite rock with coplanar double fractures was established by using discrete element numerical simulation software, and the mechanical behavior , energy, and microcrack evolution of composite rock under different fracture inclination, length and confining pressure were systematically studied. The results indicate that: ① The increase of fracture inclination angle and confining pressure has an optimization effect on the mechanical properties of the rock sample, and the increase of fracture length has a deterioration effect on it. In addition, when the composite rock changes from unidirectional stress to three-directional stress, the mechanical properties change sharply and are significantly optimized. ② With the increase of fracture inclination, length and confining pressure, the energy of composite rock presents a U-shaped distribution, decreasing and increasing law respectively, and the energy loss mainly occurs after the damage stress. ③ During the deformation and loading process of rock samples, the microcracks generated are mainly tensile cracks, while shear cracks mainly occur after damage stress. The geometric parameters of fracture and confining pressure mainly affect the evolution characteristics of microcracks at the same stress threshold.